2017
DOI: 10.1016/j.joca.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of subchondral bone abnormal changes in osteoarthritis by inhibition of SDF-1 signaling

Abstract: Higher level of SDF-1 may induce the subchondral bone abnormal changes in OA and inhibition of SDF-1 signaling could be a potential therapeutic approach for OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 41 publications
4
34
0
Order By: Relevance
“…Although the subchondral bone‐cartilage interplay is believed to contribute strongly to OA progression (Chen et al, ; Hayami et al, ; Zhen et al, ), the potential molecular signaling for the subchondral bone—cartilage interaction has been rarely investigated. Previously, it was shown that the subchondral bone‐derived TGF‐β could be released and therefore accelerate cartilage degradation in anterior cruciate ligament transection (ACLT) mice (Zhen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the subchondral bone‐cartilage interplay is believed to contribute strongly to OA progression (Chen et al, ; Hayami et al, ; Zhen et al, ), the potential molecular signaling for the subchondral bone—cartilage interaction has been rarely investigated. Previously, it was shown that the subchondral bone‐derived TGF‐β could be released and therefore accelerate cartilage degradation in anterior cruciate ligament transection (ACLT) mice (Zhen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Various signaling pathways have been found involved in the OA progression, and the modulatory role of the phosphoinositide 3‐kinase (PI3K)/protein kinase B (PKB), or AKT signaling in the pathogenesis process of OA has received substantial attentions (Chen, Wu, Sun, Dong, & Zhao, ; Chen et al, ; Dong et al, ). An upregulation of PI3K/AKT signaling in synovial fibroblasts of OA patients was recently reported (Chen, Hou, Hou, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Subchondral bone is a mechanical support of overlying cartilage and plays a critical role in bone modeling and remodeling. Lesions of subchondral bone re ect serious cartilage damage [2]. At 12 weeks, subchondral bone of pigs in two experimental groups was visibly destroyed, especially in the chemical group, which means that late OA appeared at this time; papain injection brought about more severe changes.…”
Section: Discussionmentioning
confidence: 97%
“…Osteoarthritis (OA) is a multifactorial disease characterized by synovial in ammation, extracellular matrix (ECM) degradation, and chondrocyte hypocellularity [1]. Stromal cell-derived factor-1 (SDF-1) was identi ed as a strong in ammatory cytokine existing in the synovium, and its speci c receptor C-X-C chemokine receptor type 4 (CXCR4) locates on the surface of chondrocytes [2]. The binding of SDF-1 and CXCR4 can lead to a cascade of matrix metalloproteinase (MMP) release and collagen (mostly collagen type II, Col II) and proteoglycan (mostly aggrecan, ACAN) degradation, hence exacerbating and accelerating the OA process [3].…”
Section: Introductionmentioning
confidence: 99%
“…In brief, each rat was anesthetized by administrating 0.2% (v/v) xylazine and 1% (v/v) ketamine; after being shaved and disinfected, the right knee joint was exposed through a medial parapatellar arthrotomy approach. The patella was dislocated laterally, and the knee was placed in full flexion followed by ACL and medial collateral ligament (MCL) transection with microscissors and resection of the medial meniscus . Rats were allocated randomly into four groups and received intra‐articular injections at the right knees.…”
Section: Methodsmentioning
confidence: 99%